Quantitative thresholds for 18F‐florbetaben PET for the detection of low amyloid load: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Roé‐Vellvé, Núria; Bullich, Santiago; Marquie, Marta; Barthel, Henryk; Villemagne, Victor LL; Sanabria, Angela; Tartari, Juan Pablo; Sotolongo‐Grau, Oscar; Dore, Vincent; Koglin, Norman; Mueller, Andre; Perrotin, Audrey; et al.
Abstract: Background: A pathology‐proven cutoff for NeuraCeq ( 18 F‐florbetaben) was previously developed in end‐of‐life cases to discriminate Alzheimer's disease (AD) patients from elderly Aβ‐negative non‐demented controls (NDC). However, these cutoffs could be of limited use in early stages of AD. Here, we developed and validated 18 F‐florbetaben cutoffs to detect low Aβ deposition and established amyloid pathology. Method: The low Aβ deposition threshold was derived from a sample of young healthy controls (YHC) (n=70, 27.6±5.1 y), as 2 standard deviations above the mean. The established pathology cutoff was derived using ROC curve analysis on a sample of visually determined Aβ‐negative NDC (n=62, 67.8±6.8 y) and Aβ‐positive AD dementia patients (n=62, 70.6±8.0 y). Validation was based on longitudinal samples: (1) subjective cognitive decline (SCD) volunteers (n=166; 64.9±7.2 y) and (2) mild cognitively impaired (MCI) subjects (n=45, 72.7 ± 6.5 y). The standard centiloid (CL)methodology was applied for quantification. Result: The low Aβ‐deposition detection cutoff was 13.5 CL, and the threshold for established Aβ pathology was 35.7 CL. In the validation samples, the rate of Aβ accumulation in the "low amyloid load" interval (13.5‐35.7 CL) was significantly different from zero (p<0.05), (2.1±2.1 %/year (SCD), 2.6±1.5 %/year (MCI)), which was also observed for "established Aβ deposition" (>35.7 CL) (3.4±3.2 %/y (SCD), 1.4±1.8 %/y (MCI), (p<0.05)). The accumulation rate for Aβ‐negative subjects (<13.5 CL) was not significantly different from zero (‐0.1±1.1 %/year (SCD), 0.1±1.6 %/year (MCI)). Conclusion: An interval between 13.5 and 35.7 CL is optimal for the detection of early Aβ deposition and to identify subjects that are likely accumulating Aβ. Further validation tests using additional samples are ongoing.